2021
DOI: 10.3389/fmed.2021.656615
|View full text |Cite
|
Sign up to set email alerts
|

Very-Short-Term Sleep Deprivation Slows Early Recovery of Lymphocytes in Septic Patients

Abstract: Sleep plays an important role in immune function. However, the effects of very-short-term sleep deprivation on the early recovery of immune function after sepsis remain unclear. This study was conducted in the intensive care unit to investigate the effects of 2 consecutive days of sleep deprivation (SD) on lymphocyte recovery over the following few days in septic patients who were recovering from a critical illness. The patients' self-reports of sleep quality was assessed using the Richards–Campbell Sleep Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…and adhesion molecules (vascular cell adhesion molecules, intercellular cell adhesion molecule-1, E-selectin, etc.) [ 17 , 28 31 ], suppressing LPS and TNF-α-induced increased permeability of endothelial cells [ 18 ], and alleviating post-septic intestinal injury [ 25 ]. However, the molecular mechanisms by which ANP modulates immune responses/immune cell activation are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and adhesion molecules (vascular cell adhesion molecules, intercellular cell adhesion molecule-1, E-selectin, etc.) [ 17 , 28 31 ], suppressing LPS and TNF-α-induced increased permeability of endothelial cells [ 18 ], and alleviating post-septic intestinal injury [ 25 ]. However, the molecular mechanisms by which ANP modulates immune responses/immune cell activation are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 27 ]. ANP has immunomodulatory capacity by regulating innate immunity and adaptive immunity, including increasing macrophage phagocytosis and reactive oxygen species release, enhancing natural killer (NK) cytotoxicity, promoting dendritic cell-mediated T cell polarization, stimulating the differentiation of naive CD4 + cells toward the T helper (Th) 2 and/or Th17 phenotype, inhibiting the expression of proinflammatory mediators and adhesion molecules [ 17 , 28 31 ]. We previously reported a significantly positive correlation between the plasma ANP levels and early recovery of immune function in septic patients [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with sleep apnea or sleep disordered breathing were shown to have higher rates of sepsis after medical procedures (70,71) and had increased mortality rates after a sepsis diagnosis (72); however, the contribution of sleep versus hypoxia has not been fully established in this context. A recent study by Zhang et al found that among hospitalized septic patients, those who showed poor short-term sleep quality had significantly lower blood albumin, plasma atrial natriuretic peptide, and lymphocyte counts (in particular, Tcells and NK cells) in comparison with patients with good sleep quality (73). Only a few studies have used animal models to delineate how sleep affects sepsis and endotoxemia.…”
Section: Findings Potential Impact On Sepsis Referencesmentioning
confidence: 99%
“…A retrospective study showed that hypoalbuminemia in patients with coronavirus disease 2019 was associated with illness progression to more severe stages and increased mortality [ 5 ]. Additionally, a recent study found that among patients with sepsis, the sleep deprivation group had significantly lower albumin than the good sleep group [ 6 ].…”
Section: Introductionmentioning
confidence: 99%